1989
DOI: 10.1111/j.1600-0447.1989.tb03021.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and magnesium concentrations in affective disorder: difference between plasma and serum in relation to symptoms

Abstract: Morning (0800) plasma and serum and mean diurnal (24-h) serum calcium (Ca) and magnesium (Mg) concentrations were investigated in 56 depressed patients, 32 with acute major depression, 26 of these restudied in remission, 24 patients with longstanding depression, mainly treated with lithium, and in 27 healthy controls. All subjects were rated with the Comprehensive Psychopathological Rating Scale (CPRS). Significant differences between the groups were found for 0800 and 24-h serum Ca and Mg, 0800 plasma Mg, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…The acute inflammatory response is also modulated by Mg 2+ , with neutrophil invasion reduced following SCI in animals treated with MgSO 4 (Gok et al, 2007). This correlates with studies that show that Mg 2+ deficiency evokes an inflammatory response (Malpuech--Brugère et al, 2000), including the release of pro--inflammatory cytokines and SP (Mazur et al, 2006). Mg 2+ and Substance P Within one week of Mg 2+ deficiency, plasma SP concentration was elevated (Weglicki and Phillips, 1992) and this was associated with the develop--ment of neurogenic inflammation (Weglicki et al, 1994).…”
Section: Mechanisms Of Mg 2+ Neuroprotectionsupporting
confidence: 60%
See 1 more Smart Citation
“…The acute inflammatory response is also modulated by Mg 2+ , with neutrophil invasion reduced following SCI in animals treated with MgSO 4 (Gok et al, 2007). This correlates with studies that show that Mg 2+ deficiency evokes an inflammatory response (Malpuech--Brugère et al, 2000), including the release of pro--inflammatory cytokines and SP (Mazur et al, 2006). Mg 2+ and Substance P Within one week of Mg 2+ deficiency, plasma SP concentration was elevated (Weglicki and Phillips, 1992) and this was associated with the develop--ment of neurogenic inflammation (Weglicki et al, 1994).…”
Section: Mechanisms Of Mg 2+ Neuroprotectionsupporting
confidence: 60%
“…They also reported an association between increases in plasma Mg and severity of depression and of plasma cortisol (Widmer et al, 1995). Another group reported that depressive symptoms were positively correlated with serum Mg in longstanding depression and remission, but not in acute depression (Linder et al, 1989). A further study shows the same relation in patients with unipolar depression (Hasey et al, 1993).…”
Section: Neurological Function Of Magnesiummentioning
confidence: 65%
“…Inflammatory system and magnesium Magnesium depletion has been studied for its effects on inflammatory markers. Feeding rats Mg--depleted food led to a nearly 3--fold increase in plasma IL--6, a significant increase of fibrinogen and other acute phase proteins and a significant reduction in Zn (Malpuech--Brugere et al, 2000). Mg deficiency also amplifies endotoxin--induced lethality in rats, which was correlated with increased TNFα production (Malpuech--Brugere et al, 1999).…”
Section: Neurological Function Of Magnesiummentioning
confidence: 98%
“…Induction of apoptosis mediated by oxidative stress following magnesium deprivation has been documented in several tissues. Accelerated thymus involution, a classical example of apoptosis, was found in magnesium--deficient rats (Malpuech--Brugère et al, 1999). Dietary magnesium deficiency also induced apoptosis in cardiovascular tissues (Altura et al, 2009;Tejero--Taldo et al, 2007) and in the liver (Martin et al, 2003;Martin et al, 2008).…”
Section: Extracellular Magnesium and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation